(untitled) ("Temas Sociais" Journal, 2021)
This article aims to analyze the management process of postponement of discharge of elderly patients, in the emergency service of São José Hospital, carried out by the social service team. A methodological triangulation supported in the consultation and analysis of social processes, interviews with the multidisciplinary team and documentary analysis was carried out. The objectives were centered on the definition of the user’s profile, reasons for postponement, post-discharge destination and difficulties inherent to the activity of the emergency service. Stands out as main results most patients are female, aged 81-85, with reasons for delaying mainly due to inability / unavailability of the informal support network and insufficiency / delay in the formal social response. The management of the discharge delay of the elderly is carried out by the multidisciplinary team, highlighting in this context the mediating role of the social worker in this process.